Psychosynthesis leadership coaching : a psychology of being for a time of crisis - Howard, Aubyn (London : Routledge, 2020)
Psychosynthesis Leadership Coaching responds to the call of coaches who want to be able to work with the whole person, with the inner as well as the outer worlds, and not just at rational and behavioural levels but at emotional and spiritual levels as well. Psychosynthesis is unique amongst psychologies in the emphasis it places on self and will at the centre of human psychological functioning. This holistic and integrative psychology provides the foundations for working with leaders in ways that respond to today's emergent crises. Psychosynthesis coaching is an increasingly popular approach that is finding its way into the mainstream as a response to the needs of coaching to engage at depth with emotional content and in the transpersonal realm of meaning, purpose and values. This book introduces psychosynthesis coaching to a wider audience and provides a comprehensive guide to this approach for both coaches and leaders. This book provides the context, models, methods, skills and techniques for coaches to engage with their clients within the larger context of Self and Will, alongside working on inner and outer agendas and goals of any description. For coaches, leaders and organisational practitioners alike, this approach is also about coaching our inner leader - knowing that this work always starts with ourselves.
OCLC-licensed vendor bibliographic record.
Keywords: Executive coaching; Leadership; PSYCHOLOGY / Industrial & Organizational Psychology; PSYCHOLOGY / Mental Health